Risk Factors Associated with Early Detection of Cervical Cancer by the IVA Method in Women of Childbearing Age In the City of Ternate - La Patilaiya, Hairudin; Nursia Aja; Taufik Yunus (Publisher Cv. Inara, 2021)
Background : Cervical cancer is one of the main problems in women's health in the world, including Indonesia. According to the 2018 Global Cancer Observatory from the World Health Organization (WHO), the most common cancer cases in Indonesia are breast cancer, which is 58,256 cases or 16.7% of the total 348,809 cancer cases. Cervical cancer (neck of the womb) is the second most common type of cancer in Indonesia, with 32,469 cases or 9.3% of the total cases. Objective: To determine the risk factors associated with early detection of cervical cancer using Visual Inspection with Acetic Acid (IVA) ) in women of childbearing age in the Work Area of the Ternate City Health Center for Siko Treatment. Methods: This research is a quantitative analytic study with a cross sectional design. Data collection was carried out from December 2020 to January 2021. The population was all patients who underwent examinations at the Maternal and Child Health Polyclinic (KIA) at the Siko Care Health Center in Ternate City as many as 227 patients and a sample of 145 female patients of childbearing age from January to September 2020. Techniques sampling is simple random sampling. Data analysis used univariate and bivariate with chi-square test. The research variable consists of the dependent variable, namely early detection of cervical cancer, while the independent variables are knowledge, husband's support, access to information and culture. Results: Shows that age (46.9%), knowledge of VIA (50.3%), attitude (55.2%), husband's support (52.4%), access to information (62.1%), culture (51.7%), Support Officer (48.3%), early detection of cervical cancer IVA method (55.2%), while the bivariate results include: Age (0.000, OR=19,011; CI=8.095-44,647), knowledge (0.001; OR=2.86; CI=1.563-18.367), attitude (0.000; OR=215.524 CI=53,456-868.955), husband's support (0.002; OR=1.448 CI=1.688-11.933), access to information (0.000; OR=2,294; CI=1,574-15,976), culture (0,003; OR=2,202 CI=1,648-10,717), health worker support (0,000; OR=27,111 CI;11,023-66,680). Conclusion: There is a relationship between knowledge, husband's support, access to information and culture with early detection of cervical cancer against the IVA method. Based on the results of the study, it is recommended that the relevant agencies, namely the Siko Health Center, always improve health education to the community, especially mothers and husbands regarding early detection of cervical cancer through various media tools including leaflets, posters, flipcharts and other media. Through this counseling, it is hoped that the community will be more interested and understand the material presented more quickly